Addressing Electoral Hurdles in Nigeria: Analyzing the 2023 General Elections and INEC's Role - Charles Berebon (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2023)
This paper aims to investigate the numerous challenges hindering the achievement of peaceful elections in Nigeria, with a specific focus on the 2023 general elections overseen by the Independent National Electoral Commission (INEC). Throughout Africa, several presidential and general elections have taken place, with some countries, such as Angola, Kenya, and Senegal, notably succeeding in organising free and fair electoral processes. Conversely, nations like the Democratic Republic of the Congo (DR Congo) and Nigeria have faced significant obstacles, including widespread electoral fraud and violence, despite concerted efforts to ensure credibility in their electoral systems. In 2021, the Global Conflict Barometer identified three armed conflicts each in the DR Congo and Nigeria out of a total of 20 worldwide. Elections in Nigeria have been particularly plagued by substantial violence, manipulation of ballots, vote buying, and loss of life—factors that have long hindered the country from conducting genuinely free and fair elections. Before the 2023 elections, the Independent National Electoral Commission reported attacks on at least 53 of its offices nationwide, with ongoing violence persisting. However, this paper aims to critically analyse these barriers to peaceful elections, elucidating their underlying causes and proposing solutions to foster transparent and credible electoral processes in Nigeria. Employing a method of critical analysis, the paper argues that various stakeholders, including politicians, citizens, INEC, the judiciary, and the government, must take responsibility for ensuring the successful conduct of polls. Furthermore, it advocates for the adoption of strategies akin to those employed by successful countries like Senegal, Angola, and Kenya during their elections.